Mortality and its predictors among hospitalized patients with infections due to extended spectrum beta-lactamase (ESBL) Enterobacteriaceae in Malaysia: a retrospective observational study - Abubakar, Usman; Tangiisuran, Balamurugan; Elnaem, Mohamed Hassan Abdelaziz; Sulaiman, Syed Azhar; Khan, Faiz Ullah (Springer Open, 2022)
Background: Extended spectrum beta-lactamase (ESBL) pathogens are associated with morbidity and mortality. There is a paucity of data describing the treatments and outcomes of ESBL infections in Malaysia. This study evaluated the treatments, mortality and associated factors among patients hospitalized with infections due to ESBL positive enterobacteriaceae. This is a retrospective study conducted in a tertiary hospital from January 2018 to June 2020. Hospitalized patients with ESBL-positive enterobacteriaceae infections were included. A clinical pharmacist collected data by reviewing the patients’ electronic medical records. The data were analysed using both descriptive and inferential analyses. Results: This analysis included 110 patients with a mean age of 62.1±14.4 years. Klebsiella pneumoniae (53.6%) and Escherichia coli (40.9%) were the most prevalent pathogens among the 110 infections. Bacteremia (42.7%) was the most frequent diagnosis. The isolates were resistant to majority of penicillins and cephalosporins. However, over a third (39.3%) were susceptible to piperacillin–tazobactam, while carbapenem susceptibility was extremely high (≥99%). The most frequently used empiric and defnitive antibiotics was piperacillin–tazobactam and meropenem, respectively. Less than a third (28.2%) of patients received active empiric antibiotics, and the mean duration before active antibiotics was 3.9±2.7. Overall, hospital mortality rate was 13.6%, and mortality was signifcantly associated with ICU admission (AOR 8.75; 95% CI 1.05–72.75; P=0.045) and diabetes mellitus (AOR 9.85; 95% CI 1.04–93.09; P=0.046). Conclusions: Carbapenems are the major antibiotics used to treat ESBL-positive enterobacteriaceae infections. Hospital mortality rate is relatively high and is signifcantly associated with in patients admitted to ICU and those with diabetes mellitus. Antibiotic stewardship interventions are necessary to promote early administration of active antibiotics and to reduce overuse of carbapenem antibiotics.